The Evolution of Education, Birth Rate, and Drug Dependence and their Implications for the National Security - Moraru Teodora-Ioana (Scientific Bulletin)
Education, demographic structure, and the prevalence of psychoactive substance use among young people are essential variables in assessing risks to national security. This study uses statistical data from the 2020–2024 period, obtained from official institutional sources, to identify relevant trends and correlations among these indicators. The analysis reveals a consistent decline in birth rates, a growing school dropout phenomenon, and an expansion of drug use among adolescents, with initiation occurring at increasingly early ages. These developments are examined through the lens of the human security paradigm, emphasizing how social vulnerabilities impact internal cohesion and the state's ability to manage emerging risks. The research findings support the need for integrated public policies in the fields of education, health, and security, based on contextual diagnosis and preventive intervention.